Unusual presentation of neosporosis in a neonatal puppy from a litter of bulldogs. Issue 11 (November 2016) - McAllister, MM; Funnell, O; Donahoe, SL; Šlapeta, J
Abstract : Case report: A 17‐day‐old Bulldog puppy died soon after presentation for weakness and tachypnoea. Gross lesions included diffuse pulmonary oedema and a region of myocardial pallor that resembled an infarct. Inflammation was observed histopathologically in many organs, with numerous clusters of intracellular protozoa that stained positively using Neospora caninum immunohistochemistry. Myocarditis was severe and had associated necrosis of individual myocytes, but the tissue was not infarcted. The bitch had an antibody titre of 1 : 1600 for N. caninum . All six littermates were sold and reported to be healthy at 6 months of age. Conclusion: Unusual aspects of this case include the occurrence of clinical disease in only 1 of 7 neonatal puppies, widespread dissemination of the organism in multiple tissues, and regional pallor associated with myocarditis that gave a false gross appearance of infarction. This report also adds Bulldogs to the list of dog breeds shown to be susceptible to clinical neosporosis.